Implementing The Computer-Based Technology Media to Improve Students' Motivation in Learning Process - Rahma Wati; Lianty Putri; Sumawar Pratiwi; Sima Latta (English Teaching and Linguistics Journal (ETLiJ), 2022)
Learning media is a tool that is used by someone to facilitate the delivery of material when teaching. Things like that help teachers and are a solution to make students happy when learning and not feel bored. Learning using computer technology learning media is more widely used now. Some of them were successful but some also failed. The media is expected to be able to provide concrete experiences, motivation to learn, enhance absorption and retention of student learning. As for that we have conducted practice and interviews related to this 'Implementing The Computer-Based Technology Media to Improve Students' Motivation in Learning Process' research in three primary schools, they are (1.) SDS Sentosa 10220797, (2.) SDN 065008, and (3.) SDS Jabal Nur 69992640, each student has different opinion about the application of technology that can be used as a reference and introspection to improve the use of learning through computer technology/presentation media.